2021
DOI: 10.1038/s41419-021-03720-w
|View full text |Cite
|
Sign up to set email alerts
|

SMYD2 promotes tumorigenesis and metastasis of lung adenocarcinoma through RPS7

Abstract: The protein methyltransferase SET and MYND domain-containing protein 2 (SMYD2) is a transcriptional regulator that methylates histones and nonhistone proteins. As an oncogene, SMYD2 has been investigated in numerous types of cancer. However, its involvement in lung cancer remains elusive. The prognostic value of SMYD2 expression in lung adenocarcinoma (LUAD) was determined through bioinformatics analysis, reverse-transcription polymerase chain reaction, western blotting, and immunohistochemistry. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…SMYD2 expression was found to be highly upregulated in lung adenocarcinoma, and high SMYD2 expression was linked to shorter overall and disease-free survival. Mechanically, SMYD2 may promote carcinogenesis and metastasis by activating RPS7 transcription through binding to its promoter [ 24 ]. Inhibition of SMYD2 expression has been shown to significantly reduce cervical cancer proliferation in vivo and in vitro [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMYD2 expression was found to be highly upregulated in lung adenocarcinoma, and high SMYD2 expression was linked to shorter overall and disease-free survival. Mechanically, SMYD2 may promote carcinogenesis and metastasis by activating RPS7 transcription through binding to its promoter [ 24 ]. Inhibition of SMYD2 expression has been shown to significantly reduce cervical cancer proliferation in vivo and in vitro [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…RPS7, in its full name small ribosomal protein subunit 7, is an essential part of the small subunit of ribosomes, and it participates in the bioprocess of protein synthesis in normal states [ 29 ]. Previous publications revealed that RPS7 is involved in the progression of various malignancies, such as prostate cancer and lung cancer [ 29 , 30 ], but its role in renal injuries and ferroptosis has not been investigated. TRIB3, in its full name tribbles pseudokinase 3, was reported to play a pivotal role in cellular stress response [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study aimed to investigate the function of SMYD2 in PDAC using mouse and cellular models found evidence that SMYD2 plays a pivotal role in the development of this deadly pancreatic cancer[ 16 ] (Figure 1B ). In other human cancers, SMYD2 usually exerts its tumorigenic effects through methylating cell signaling-related proteins and through the effect of such methylation on the targets’ activity, stability, or subcellular localization[ 13 , 27 , 42 , 48 ]. Such a methylation-oriented mechanism has been instrumental for the initial development of a mechanistic hypothesis of SMYD2 involvement in PDAC and for the subsequent success of establishing a novel link of SMYD2 to promoting PDAC growth and progression[ 16 ].…”
Section: Current Evidence Of Smyd2 Involvement In Pancreatic Cancermentioning
confidence: 99%
“…These pathways include the critical signaling cascade RTK/Ras, the downstream signaling cascades of the RTK/Ras pathway, such as the mitogen-activated protein kinase (MAPK) pathway, and the PI3K/AKT pathway[ 16 , 27 , 28 , 30 , 31 ]. As dysregulation of these signaling pathways is an almost universal phenomenon in cancer, it is not surprising that SMYD2 overexpression has been linked with tumor development and progression in multiple human cancers, such as gastric cancer[ 33 ], esophageal squamous cell carcinoma[ 34 ], breast cancer[ 30 ], bladder cancer[ 23 ], colon cancer[ 31 , 35 ], colorectal cancer[ 36 ], hepatocellular carcinoma[ 14 ], acute lymphoblastic leukemia[ 37 , 38 ], hematopoietic leukemias[ 39 ], head and neck squamous cell carcinoma[ 15 ], lung adenocarcinoma[ 13 ], papillary thyroid carcinoma[ 40 ], cervical cancer[ 41 , 42 ], ovarian clear cell carcinoma[ 43 , 44 ], and renal cell carcinoma[ 45 , 46 ] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%